USING THE TEACHING OF MAHMUD AZ ZAMAXHARI IN IMPROVING THE SYSTEM OF SPIRITUAL AND MORAL EDUCATION OF STUDENTS (World Bulletin of Social Sciences, 2023)
In this article, the design, planning, organization, control and management of the educational process aimed at improving the spiritual and moral education of requirements in the higher education system through the works of Mahmud Zamakhshari and the new worldview that ensures the effectiveness of this process. Teacher training is important. Mahmud Zamakhshari's educational views are of special importance in the history of pedagogical teachings. Despite the fact that Mahmud Zamakhshari's scientific and spiritual heritage has been widely studied in the East and West, there is a need to study his spiritual heritage pedagogically. Development of the highest qualities of spiritual and moral education in students of higher educational institutions during the study of the spiritual and moral heritage of Alloma is an urgent social and pedagogical problem
Keywords: Spirituality; morals; education